2011
DOI: 10.1002/app.34244
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization of polyethylene oxide/silver nanoplate composites

Abstract: This research was accomplished to investigate the kinetics of isothermal crystallization of polyethylene oxide (PEO)/silver nanoplate composites. It was obtained that the spherulites increased in size and numbers with time for the composites with various particle loadings. Additionally, the spherulite growth rate of composites decreased with an increase in the crystallization temperature and increased with the addition of nanoplates. The spherulite growth rate was further analyzed by the theory developed by La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…However, a different crystallization behavior was also reported for PEO in the literature, i.e. nanoparticles decreased the T c to hinder the PEO crystallization [44][45][46]. In the present study, it seems that neither GnP nor FGnP have significant effect on the nucleation density of PEO crystallites.…”
contrasting
confidence: 46%
“…However, a different crystallization behavior was also reported for PEO in the literature, i.e. nanoparticles decreased the T c to hinder the PEO crystallization [44][45][46]. In the present study, it seems that neither GnP nor FGnP have significant effect on the nucleation density of PEO crystallites.…”
contrasting
confidence: 46%
“…Because σ relates to the segmental nature of polymer chains as reflected by the characteristic ratio ( C ∞ ), a constant σ regardless of the filler content indicates that the presence of NPs does not cause chain extension during crystallization. This assumption has been used with various blends and composite systems . Following this assumption and taking σ = 10 erg cm −2 , σ e was determined (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This assumption has been used with various blends and composite systems. 29 Following this assumption and taking σ = 10 erg cm −2 , 28 σ e was determined ( Table 1). Under our experimental condition, K g decreases from 3.65 × 10 4 to 3.36 × 10 4 with the addition of SiO 2 NPs.…”
Section: Effect Of Sio 2 Content On Isothermal Crystallization Of Peomentioning
confidence: 99%
“…Adhikari and Lozano used DSC to investigate the crystallization behavior of PEO/carbon nanofiber systems under nonisothermal conditions and showed that all carbon nanofiber loadings retard the crystallization of PEO [25]. The effect of two-dimensional silver nanoplatelets on the non-isothermal crystallization of PEO has been discussed by Rahmansyah et al [26,27]. They found that the overall crystallization rate of nanocomposites was slower than that of neat PEO and the radius of spherulites was greater.…”
Section: Introductionmentioning
confidence: 96%